Partisipasi Masyarakat dan Kualitas Pengelolaan Keuangan Desa Survey pada Desa Kecamatan Masjid Raya Aceh Besar - Indriani, Mirna; Nadirsyah, Nadirsyah; Fahlevi, Heru; Putri, Safrida (Jurnal Riset Akuntansi dan Keuangan, 2019)
This research was conducted to investigate whether the level of community participation influences the quality of village financial management. Tests were carried out on 144 samples consisting of community elements namely hamlet heads (kepala dusun), BPDes/tuha peut, PKK, youth leader, imeum meunasah, panglima laot, and ketua blang/farmer representative. Data collection is done by distributing questionnaires. Data were analyzed using structural equation models using LISREL 8.80 software. The results showed that the level of community participation has a positive relationship to the quality of village financial management means that the higher the level of community participation, the better the quality of village financial management